2016
DOI: 10.1590/18069657rbcs20150383
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Heavy Metals/Metalloid on Multi-Metal Contaminated Soil Samples from a Gold Ore Processing Area: Effects of Humic Substances

Abstract: Bioavailability of heavy metals at contaminated sites is largely controlled by the physicochemical properties of the environmental media such as dissolved organic matter, hydroxides and clay colloids, pH, soil cation exchange capacity and oxidation-reduction potential. The aim of this study was to investigate soil pH and heavy metal solubility effect by levels of humic and fulvic acids applied in soil samples with different levels of contamination by heavy metals. The soil samples used in this study were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
1
3
0
2
Order By: Relevance
“…Their results also showed that Pb and Cd immobilized in co-precipitation complexes were similar to their adsorption. The result of this study corresponds to that suggested by Boechat et al (2016), where humic and fulvic acids substantially declined in selected heavy metals, including Pb and Cd. The soil sample used in this study exhibits different retention of Pb and Cd where Inceptisols retains Pb and Cd higher than Entisols, as indicated by the amount of soluble form of both metals (Figures 2 and 3).…”
Section: Discussionsupporting
confidence: 89%
“…Their results also showed that Pb and Cd immobilized in co-precipitation complexes were similar to their adsorption. The result of this study corresponds to that suggested by Boechat et al (2016), where humic and fulvic acids substantially declined in selected heavy metals, including Pb and Cd. The soil sample used in this study exhibits different retention of Pb and Cd where Inceptisols retains Pb and Cd higher than Entisols, as indicated by the amount of soluble form of both metals (Figures 2 and 3).…”
Section: Discussionsupporting
confidence: 89%
“…On this line, few studies have investigated chitosan and humic acids (that are natural constituents of the soil) to extract heavy metals from highly heavy metal polluted soil (Kulikowska et al, 2015a;Boechat et al, 2016;Jiang et al, 2011;Meng et al, 2017;Gusiatin et al, 2017). Nowadays cheaper sources of humic substances are under research.…”
Section: New Aproaches Regarding Remediation Methods Of Heavy Metals mentioning
confidence: 99%
“…The effect of organic matter on contaminant or nutrient availability is highly influenced by the different forms or fractions of organic matter. The reactivity of DOC is influenced by the proportion of fulvic and humic acids contained within it (Boechat et al, 2016). Fulvic acids (FA) are soluble at all pH conditions while humic acids (HA) are only soluble at alkaline pH values.…”
Section: Bioavailability Of Unamended Soilsmentioning
confidence: 99%